SPE Asia Pacific Oil and Gas Conference and Exhibition 2013
DOI: 10.2118/165895-ms
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Imaging of Fluid Mobility in Low-Permeability Rocks Using High-Resolution Positron Emission Tomography

Abstract: Positron emission tomography (PET) continues to have wide-ranging medical application and is based on the detection of gamma radiation emitted from the decay of certain types of radionuclides. Modern PET scanners produce three-dimensional (3D) images of the radiation source, in discrete time steps, using tomography analysis. This paper presents an application of PET for studying fluid mobility in pressurized low-permeability rocks in the presence of natural fractures. This technique uses a high-resolution PET … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…4 to 9 in (Maučec et al 2013c). However, at this stage of analysis, it still cannot be confirmed that the PET technique can quantitatively image microscopic flow through the actual fracture as a prerequisite for determining the flow and velocity profiles within the fracture.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…4 to 9 in (Maučec et al 2013c). However, at this stage of analysis, it still cannot be confirmed that the PET technique can quantitatively image microscopic flow through the actual fracture as a prerequisite for determining the flow and velocity profiles within the fracture.…”
Section: Discussionmentioning
confidence: 98%
“…The experimental setup and the results of the first proof-of-principle measurements of fluid front movement in sandstone cores in time-lapse mode were initially presented in Maučec et al (2013a). The findings on the imaging of individual core fractures or cracks in naturally fractured shale cores are elaborated in greater detail in Maučec et al (2013b) and Maučec et al (2013c). The findings on the imaging of individual core fractures or cracks in naturally fractured shale cores are elaborated in greater detail in Maučec et al (2013b) and Maučec et al (2013c).…”
Section: Introductionmentioning
confidence: 99%
“…A 3D image can be constructed from a collection of such LORs, measured at many angles, using tomography analysis. Further details on the PET method are presented by Maučec et al (2013aMaučec et al ( , 2013bMaučec et al ( , 2013c and in references therein (e.g., Saha 2010).…”
Section: Methodsmentioning
confidence: 99%
“…While the confining pressure for the sandstone cores was sufficient at 500 psi (Maučec et al 2013a(Maučec et al , 2013b(Maučec et al , 2013c, for all of the naturally fractured shale core experiments, higher operating pressures and an alternative injection approach were required to ensure reasonable flow through the column. The shale core dimensions were 1-in.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation